2005
DOI: 10.1016/j.febslet.2005.03.043
|View full text |Cite
|
Sign up to set email alerts
|

The yeast eIF4E‐associated protein Eap1p attenuates GCN4 translation upon TOR‐inactivation

Abstract: Amino acid-starved yeast activates the eIF2a kinase Gcn2p to suppress general translation and to selectively derepress the transcription factor Gcn4p, which induces various biosynthetic genes to elicit general amino acid control (GAAC). Well-fed yeast activates the target of rapamycin (TOR) to stimulate translation via the eIF4F complex. A crosstalk was demonstrated between the pathways for GAAC and TOR signaling: the TOR-specific inhibitor rapamycin activates Gcn2p. Here we demonstrate that, upon TOR-inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…This later notion is supported by our binding experiments in which we found that under ER-stress conditions (where mTORC1 activation is reduced and P-eIF2α signaling is increased) Rheb losses it’s interaction with mTOR but remain bound to PERK (Figure 4G). As cell growth and ER stress is intimately connected (Tsang et al, 2010), such dynamic binding of Rheb may regulate normal physiology to reciprocally alter mTOR and P-eIF2α signaling, as observed in various cell types (Anand and Gruppuso, 2006; Deng et al, 2002; Hara et al, 1998; Kato et al, 2012; Kim et al, 2002; Koumenis et al, 2002; Kubota et al, 2003; Liu et al, 2006; Matsuo et al, 2005; Schneider et al, 2008; Tee and Proud, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This later notion is supported by our binding experiments in which we found that under ER-stress conditions (where mTORC1 activation is reduced and P-eIF2α signaling is increased) Rheb losses it’s interaction with mTOR but remain bound to PERK (Figure 4G). As cell growth and ER stress is intimately connected (Tsang et al, 2010), such dynamic binding of Rheb may regulate normal physiology to reciprocally alter mTOR and P-eIF2α signaling, as observed in various cell types (Anand and Gruppuso, 2006; Deng et al, 2002; Hara et al, 1998; Kato et al, 2012; Kim et al, 2002; Koumenis et al, 2002; Kubota et al, 2003; Liu et al, 2006; Matsuo et al, 2005; Schneider et al, 2008; Tee and Proud, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic and genetic studies suggest that mTOR signaling does influence phospho-eIF2α. For instance, the mTOR inhibitor, rapamycin, is known to upregulate phospho-eIF2α in some cells (Anand and Gruppuso, 2006; Kato et al, 2012; Kubota et al, 2003; Matsuo et al, 2005). Similarly, heat inactivation of mTOR potentiates phospho-eIF2α in yeast cells, whereas the genetic deletion of PTEN, a negative regulator of mTOR, reduces phospho-eIF2α in cancerous cells (Mounir et al, 2009; Valbuena et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a related note, the yeast eIF4E-associated protein Eap1, which inhibits cap-dependent translation initiation via the TOR signaling cascade, attenuates induction of Gcn4 translation (48). Recent work has shown that overexpression of eIF4E-BP, the Eap1 functional equivalent in Drosophila , rescues Parkinsonian phenotypes in fly models of Parkinson disease by inhibiting cap-dependent translation and thereby inducing expression of genes involved in stress response (49).…”
Section: Discussionmentioning
confidence: 99%
“…Deregulating initiation by overexpression of the CAP-binding protein eIF4E leads to malignant transformation and therefore, not surprisingly, eIF4E is elevated in many human cancers (De Benedetti and Rhoads 1990;Lazaris-Karatzas et al 1990). In addition, TOR signaling and stress situations including membrane defects inhibit global initiation of translation by regulating binding of proteins (4E-BPs) to the initiation factor eIF4E (Cosentino et al 2000;Deloche et al 2004;Matsuo et al 2005;Ibrahimo et al 2006).…”
Section: Discussionmentioning
confidence: 99%